The shading quality of tree species and their influence on the microclimate of the immediate surroundings in urban environments (Periodicals of Engineering and Natural Sciences, 2022)
The purpose of this paper was to assess the quality and impact of the shading offered by two types of shading trees Samanea saman (rain tree) and Searsia Pendulina (Wit Karee) of the environmental variables Dry Bulb Temperature (TBS) and Radiant Thermal Load (CTR) by selected species trees and increasing their relative air humidity (RH) on the climatic conditions of the University of Baghdad, and Baghdad Park in An Nasiriyah, Iraq. Data related to the variables described were collected by means of two sets of thermometers placed: the one in tree shade (5 m) and the second in trunk (full sun) at 10 m, from June to August 2020, for each single tree, for 3 days each hour from 10:00 am to 14:00 pm. The calculation of the percentage of the Relatively Variated Values, at 5 m and 10 m, with respect to the values obtained at 5 m for quantification of shading contribution to the attenuation and augmentation of environmental variables took place. The data were analysed by testing the following hypotheses: I TBS shade attenuation > TBS attenuation at 10 m (ii) shade CTR attenuation > CTR attenuation at 10 m and (iii) shade RH increased > RH increase at 10 m. Increased shade of TBS at 10 m. The results show the good impact on TBS and CTR mitigation and RH increases. Searsia Pendulina was the most prominent species that exhibited a general TBS attenuation range from 5% to 10%, rain tree and Karee in the UR variable with increments over 30% and Karee in the CTR shadow rates with attenuations in the order of 15%. The comparison of results in this sector with the criterion of comfort has proved the impact on improving the microclimate of the local environment of the researched arboreal species.